1987
DOI: 10.1104/pp.83.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Barley Mutants Lacking Chloroplast Glutamine Synthetase—Biochemical and Genetic Analysis

Abstract: In the F2 generation, nonviability in air and the lack of chloroplast glutamine synthetase co-segregated, in both the lines tested. These two lines and four others proved to be allelic, we designate them gin 2a-f. The characteristics of these mutants conclusively demonstrate the major role of chloroplast glutamine synthetase in photorespiration and its associated nitrogen recycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
223
1
2

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(248 citation statements)
references
References 11 publications
15
223
1
2
Order By: Relevance
“…Furthermore, molecular studies have shown that under photorespiratory conditions the gene encoding the chloroplast isoenzyme of GS was induced 4-fold (Edwards and Coruzzi, 1989). These results support the earlier findings of Wallsgrove et al (1987), which suggested that GS/GOGAT played a key role in the reassimilation of ammonia released during photorespiration. However, GDH may play a complementary role to GS/GOGAT in the reassimilation of excess ammonia released during stress conditions or during specific stages of development (Yamaya et al, 1986;Rhodes et al, 1989; for review, see Stewart et al, 1980;Srivastava and Singh, 1987).…”
supporting
confidence: 81%
“…Furthermore, molecular studies have shown that under photorespiratory conditions the gene encoding the chloroplast isoenzyme of GS was induced 4-fold (Edwards and Coruzzi, 1989). These results support the earlier findings of Wallsgrove et al (1987), which suggested that GS/GOGAT played a key role in the reassimilation of ammonia released during photorespiration. However, GDH may play a complementary role to GS/GOGAT in the reassimilation of excess ammonia released during stress conditions or during specific stages of development (Yamaya et al, 1986;Rhodes et al, 1989; for review, see Stewart et al, 1980;Srivastava and Singh, 1987).…”
supporting
confidence: 81%
“…The activity of the promoter for chloroplast GS2 predominantly in photosynthetic cell types is consistent with findings that chloroplast GS2 functions in the reassimilation of photorespiratory ammonia (7,17) and in the assimilation of reduced nitrite in plastids (8). Previous analysis of photorespiratory mutants revealed that plants that lacked chloroplast GS2 were nonviable when grown under photorespiratory conditions even though they contained normal levels of cytosolic GS (7).…”
Section: Discussionsupporting
confidence: 60%
“…Early biochemical data revealed that GS functions in the assimilation of ammonia generated by numerous plant processes, which include seed germination (4,5), photorespiration (6,7), nitrite reduction (8), nitrogen-fixation in root nodules (9,10), and primary ammonia assimilation from the soil (11). An analysis of the GS genes in several species has revealed a strong correlation of individual GS gene expression with specific aspects of plant development (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…1 within mesophyll cells (Keys et al, 1978). GS2 is crucial for the reassimilation of this NH 4 1 , because mutants lacking this enzyme accumulate NH 4 1 and die (Wallsgrove et al, 1987). Although GDH activity is usually very low in mesophyll cells compared with GS2 (Bechtold et al, 1998), several studies have provided evidence that mesophyll GDH may reassimilate small amounts of photorespiratory NH 4 1 (Hartmann and Ehmke, 1980;Neeman et al, 1985;Yamaya et al, 1986 1 ] produce more labeled Glu and Gln than controls (Ameziane et al, 2000;Mungur et al, 2005).…”
Section: Gdh Isoenzyme 1 In Roots Catabolizes Glumentioning
confidence: 99%